Developing a performance correlation for counter-flow regenerative indirect evaporative heat exchangers with experimental validation. (5th September 2016) - Cui, X.; Islam, M.R.; Mohan, B.; Chua, K.J.
Highlights: The performance correlation for counter-flow regenerative IEHX is developed. Three dimensionless groups are identified to evaluate the thermal performance. The empirical constants are determined via data-fitting from simulation results. Experimental study is conducted to validate the developed correlation. Abstract: The present article aims to determine a minimum parametric representation for evaluating the thermal performance of a counter-flow regenerative IEHX (indirect evaporative heat exchanger). Three dimensionless groups have been identified in order to develop a performance correlation based on non-dimensional forms of the governing equations. Numerical simulations were carried out to determine the empirical constants of the correlation by fitting the simulated dimensionless outlet temperature as a function of each dimensionless group. Simulations have been conducted by changing the value of each dimensionless group while keeping a constant value for other parameters. The simulated dimensionless outlet temperature was varied from 0.20 to 0.73. A prototype of a counter-flow regenerative IEHX was designed and experimentally studied. The correlation was validated by comparing the calculated results with experimental findings as well as published experimental data acquired from literature. The developed correlation is able to predict the performance of the counter-flow regenerative IEHX within a discrepancy of 12%. We further demonstrated that the correlation could be a practical approach to predict the performance and optimize the configuration of the IEHX.